Not just a passing FAD: Insights from the use of artisanal fish aggregating devices for food security in Kiribati. (January 2016) - Campbell, Brooke; Hanich, Quentin; Delisle, Aurélie
Abstract: Fish are a significant food source for Pacific Island Countries and Territories (PICTs), but current projections indicate future supply shortfalls and distribution gaps in some PICTs. Regional and national food security strategies are accordingly seeking practical activities to improve food security benefits from fisheries. Expanding the use of artisanal Fish Aggregating Devices (FADs) is a popular method of meeting these objectives. However, FAD-associated food security benefits are not being fully realized in some PICTs because of key policy and management barriers. We identify and then discuss some of these barriers in the context of Kiribati, a small island developing State in the Pacific that is heavily dependent on fish for food and livelihood benefits. We find that in the rush to deliver visible short-term results, project resources are often unevenly allocated to deployment activities rather than across the breadth of policy and management activities required to realistically achieve food security objectives. We propose that more precautionary, cooperative, context-specific, and integrated regional and domestic policy responses to artisanal FAD use are needed if Kiribati's food fish security goals are to be better realized in practice. Highlights: We investigate whether FAD food security benefits are being fully realised in Kiribati. We identify and discuss barriers to FAD food security benefit delivery. Unevenly allocated FAD resources are a barrier to meeting food security objectives. More precautionary, context-specific, and integrated policy responses are necessary.